Mobilization of bone marrow mesenchymal stem cells in vivo augments bone healing in a mouse model of segmental bone defect - Kumar, Sanjay (2012)
Although the number of mesenchymal stem cells (MSC) in the bone marrow is sufficient to maintain skeletal homeostasis, in osteopenic pathology, aggravated osteoclast activity or insufficient osteoblast numbers ensues, affecting normal bone remodeling. Most of the currently available therapies are anti-resorptive with limited osteogenic potential. Since mobilization of stem/progenitors from the BM is a prerequisite for their participation in tissue repair, amplification of endogenous stem cells may provide an alternative approach in these conditions. The present study determined the potential of MSC mobilization in vivo, using combinations of different growth factors with the CXCR4 antagonist, AMD3100, in a mouse model of segmental bone defect. Results indicated that among several factors tested IGF1 had maximum proliferative ability of MSC in vitro. Results of the in vivo studies indicated that the combination of IGF1 and AMD3100 provided significant augmentation of bone growth as determined by DXA, micro-CT and histomorphometry in mice bearing segmental fractures. Further, characterization of MSC isolated from mice treated with IGF1 and AMD3100 indicated Akt/PI3K, MEK1/2-Erk1/2 and smad2/3 as key signaling pathways mediating this effect. These data indicate the potential of in vivo stem cell mobilization as a novel alternative for bone healing.